African honey bees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The Management of African Honey Bees including the Design of Low Cost Hives International Bee Research Association 18 North Road Cardiff, CF1 3DY UK. Fax: +44 1222 665522.